Report of Meeting: The Ninth Katowice–Debrecen Winter Seminar on Functional Equations and Inequalities, Będlewo (Poland), February 4–7, 2009 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2009)
Report of Meeting: The Ninth Katowice–Debrecen Winter Seminar on Functional Equations and Inequalities, Będlewo (Poland), February 4–7, 2009.